Performance of composite reinforced short column under axial loading - Chaitanya, N; Ranga Rao, V; Achyutha Kumar Reddy, M (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to compare the behaviour of composite reinforced concrete square short columns and conventional square short column. Experiments are conducted on four axially loaded column specimens till failure. Among four specimens, two are conventional and remaining two columns are having equal angles as main reinforcement. Short columns are designed using IS 456 2000. The obtained details of main reinforcement are replaced in area wise by equal angle (ISA 2525). The tie reinforcement used to withhold the main reinforcement in position are retained with the same deformed bars. Performance of columns are measured in terms of load carrying capacity, longitudinal strain, stress, crushing modes, strains in each face using strain gauges. Outcome of the experiments are compared and plotted in the form of stress vs strain of the column. A finite element model was developed using Abaqus to simulate the results.Â Â